Understanding Kerje Sara Urang in the Gayo Community of Belah Hakim: A Study of ʿUrf and Local Customary Practices - Adelin Hakim; Abdul Manan; Jailani Jailani; Nufiar Nufiar; Khairiah Syahabuddin (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the kerje sara urang prohibition within the Gayo community's Belah Hakim clan, a customary rule forbidding intra-clan marriage, utilizing a qualitative method with an empirical juridical approach. The research combines normative analysis with direct field observation in Belah Hakim in habited areas of Central Aceh, Bener Meriah, and Gayo Lues. Primary data were gathered through interviews, observation, and documentation, analyzed using the Miles and Huberman model and triangulated for validity. The study found that the Belah Hakim community enforces this prohibition due to beliefs in shared lineage impacting health, its role in maintaining social harmony, fear of ancestral curses, and a desire to uphold religious values. Violators face parak (exile for six-months) and traditional fines, with more severe sanctions like jeret naru (permanent exile) for specific cases. From an ‘urf perspective, this prohibition is categorized as al-’urf al-fāsid because it lacks explicit Islamic legal basis and can lead to harmful social consequences such as family disintegration, social exclusion, and infringement on individual rights, while also risking shirk through beliefs in ancestral curses. This research highlights the conflict between customary norms and Islamic justice, advocating for a contextual Islamic legal approach to align customary law with maqāṣid al-sharī'ah.